Penerapan Data Mining Menggunakan Algoritma Apriori pada Brand Milenials Cafe - Hadi Gunawan; Tundo Tundo; Devika Azahra Ramadhani; Farhan Adriansyah Waloeya (Universitas Methodist Indonesia, 2024)
Millennials Café is a cafe that just opened in March 2024, in an effort to stay relevant and competitive in this field, Millennials Café needs to continue to innovate and adjust to customer preferences. One way is to utilize data mining technology. The Apriori algorithm is one of the data mining technologies that can be used. The application of the apriori algorithm to the Milenials Café transaction data aims to find association rules to be able to generate frequencies and relationships between one or more items in the transaction data in the Milenials Café. This research produces 33 association rules that can help the sales strategy at Milenials Café. The following are the association rules with the highest confidence value, namely the Thai Tea menu, Milo Dinasourus, 100% Millennials Pizza, Hezelnut Chocolate, Oreo Cookies and Cream Shake 97%. Millennials Pizza, Fried Potatoes 96%. The 33 rules that already exist can be used as a reference for the owner of Millennials Café to create a sales strategy that can increase cafe revenue.